The Armenian question before the Peace conference - (:unkn) unknown (My University)
On February 26, 1919, a joint memorandum was presented to the Paris Peace Conference at Versailles by Boghos Nubar, President of the Armenian National Delegation, and Avetis Aharonian, President of the Delegation of the Armenian Republic. The document requested international recognition of an independent Armenia, incorporating the Caucasus Republic and Western (Ottoman) Armenia
A memorandum presented officially by the representatives of Armenia to the Peace conference at Versailles, on February 26th, 1919
[New York. - Press Bureau, The Armenian National Union of America, 1919].- 74 p. ; 29 cm.- Notes: Cover title signed by A. Aharonian, President of the Delegation of the Armenian Republic, and B. Nubar, President of the Armenian National Delegation, Feb. 12, 1919
Գիրքը ՀԱԳ- ում բացակայում է։ Տվյալները՝ ԱՄՆ-ի Կոնգրեսի գրադարանից
https://archives.webaram.com/dvdk_new/eng/the-armenian-question-before-the-peace-conference-1919_OCR.pdf
Keywords: World War, 1914-1918-Territorial questions-Armenia